2015
DOI: 10.1016/j.bbrc.2015.05.032
|View full text |Cite
|
Sign up to set email alerts
|

mTOR is necessary for proper satellite cell activity and skeletal muscle regeneration

Abstract: The serine/threonine kinase mammalian target of rapamycin (mTOR) is a key regulator of protein synthesis, cell proliferation and energy metabolism. As constitutive deletion of Mtor gene results in embryonic lethality, the function of mTOR in muscle stem cells (satellite cells) and skeletal muscle regeneration remains to be determined. In this study, we established a satellite cell specific Mtor conditional knockout (cKO) mouse model by crossing Pax7CreER and Mtorflox/flox mice. Skeletal muscle regeneration aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
86
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(94 citation statements)
references
References 29 publications
6
86
0
2
Order By: Relevance
“…This might account for the global increase of Pax7 expression between day 0 and day 3 of culture in all treatment groups. The increase in MyoD expression that is observed between day 0 and day 3 in all groups supports this theory, as proliferating satellite cells are characterized by co-expression of MyoD and Pax7 [81]. Additionally, it has been demonstrated that, even in immortalized cell lines such as C2C12, not all cells undergo myogenic differentiation as a subset remains in quiescence [82].…”
Section: Discussionmentioning
confidence: 72%
“…This might account for the global increase of Pax7 expression between day 0 and day 3 of culture in all treatment groups. The increase in MyoD expression that is observed between day 0 and day 3 in all groups supports this theory, as proliferating satellite cells are characterized by co-expression of MyoD and Pax7 [81]. Additionally, it has been demonstrated that, even in immortalized cell lines such as C2C12, not all cells undergo myogenic differentiation as a subset remains in quiescence [82].…”
Section: Discussionmentioning
confidence: 72%
“…These cells are a small fraction of the muscle cells in a tissue, but can be studied in vivo after muscle damage or ex vivo in culture proliferation and differentiation models. The mTOR pathway has a stimulatory role at several steps in the differentiation process of satellite cells and a full description is beyond the scope of this review (Rodgers et al, 2014; Schiaffino et al, 2013; Zhang et al, 2015). Continued studies of the role of mTOR in muscle are important given that the signaling pathway is critical in both the metabolic functions of differentiated fibers, as well as regeneration of new ones.…”
Section: Mtor a Metabolic Master Regulatormentioning
confidence: 99%
“…Approximately 30 mg of tissue was used for RNA extraction using the TRIzol Reagent (Invitrogen, Life Technologies), according to manufacturer's instructions. The quality and concentration of total RNA were measured by a spectrophotometer (Nanodrop 3000, ThermoFisher), as described previously (84). cDNA was prepared using the RT 2 first strand kit following the manufacturer's instructions (Qiagen, Valencia, CA).…”
Section: (Treestar)mentioning
confidence: 99%